Together we must... : end violence against women and girls and HIV & AIDS : a review of promising practices in addressing the intersection - Drezin, Jenny (UNIFEM New YorkUS, 2009)
Focuses on four broad-based strategies for tackling the problems viz. community mobilization to transform harmful gender norms; engagement of marginalized groups that are often more vulnerable to the twin pandemics development of integrated approaches to support and care; and advocacy for greater accountability among funding agencies and policy makers.